HTM2: Spatial Toolkit for the Virtual Observatory - Fekete, Gyorgy; Szalay, Alex; Gray, Jim (Astronomical Data Analysis Software and Systems XIII, ASP Conference Series, 2003)
The hierarchical tringular mesh (HTM) is a discrete foundation for describing location, size and shape on the celestial sphere. Indices derived from HTM descriptors are used in a relational database for managing spatial information. Some of the new features available in the current implementation support operations such as the ability to perform searches based on arbitrary polygons, convex hulls of polygons or any region bounded by great or small circles. These functions are reached through a language that is implemented as an extension to MSQL Server 2000 relational database engine. The heart of the HTM tools can also be used through various interfaces in several langugages, like C++, C# and Java. An extensive XML specification for describing spatial structures to support spatial queries is also under development.